Does Having Knowledge About Collateral Circulation Affect Patient Selection in Mechanical Thrombectomy? - Fatma Ger Akarsu; Özlem Aykaç; Hayri Demirbaş; Atilla Özcan Özdemir (Türk Nöroloji Dergisi, 2021)
Endovascular thrombectomy is a well-known effective treatment in the first six hours of acute ischemic stroke, but endovascular therapy is also efficient in patients admitted six hours after symptom onset. The RAPID software is a powerful tool that processes computed tomography perfusion data and predicts ischemic core size and collateral status for endovascular treatment in these patients. Presented herein is a 66-year-old female patient with acute right middle cerebral artery occlusion with a symptom onset of >6 h. The reason why mechanical thrombectomy was not performed despite volume loss in the patient’s perfusion imaging is also discussed. Brain hemodynamics is undeniably different in every patient, and this should be kept in mind while evaluating imaging methods based on blood flow, such as the RAPID software. Therefore, this report aimed to present a patient that demonstrated the importance of patient-based selection in acute ischemic stroke treatment.